Analisis Penggunaan Media Pembelajaran dalam Pembelajaran Pendidikan Pancasila di Sekolah Dasar: Studi Literatur - Afrijal Rizki Saputra; Bunga Amelia Evayanti; Indri Rahmawati; Selvy Mar'atul Azizah (Universitas PGRI Madiun, 2026)
Despite these benefits, the integration of learning media into classroom instruction continues to encounter several obstacles, including teachers' limited professional competence, insufficient innovation in choosing appropriate instructional media, and inadequate educational infrastructure. This study was conducted to analyze the utilization of learning media in elementary school Pancasila Education using a qualitative literature review approach. The analysis was based on nine relevant articles published in national scientific journals, with the data examined through content analysis involving data reduction, data organization, and conclusion formulation. The review demonstrates that both conventional and digital media positively influence students' learning motivation, classroom engagement, and comprehension of Pancasila Education content. However, the success of media implementation is strongly affected by teachers' professional capabilities, the suitability of the selected media for instructional objectives, and the availability of adequate learning facilities. Accordingly, strengthening teachers' competencies and improving educational resources are essential to maximize the effectiveness of learning media in Pancasila Education at the elementary school level.